2022
DOI: 10.1021/acs.orglett.2c00454
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Divergent C–H Functionalization Reaction of Quinoxalin-2(1H)-ones and Alkynes Controlled by N1-Substituents for the Synthesis of (Z)-Enaminones and Furo[2,3-b]quinoxalines

Abstract: With control by N1-substituents, the switchable divergent C−H functionalization reaction of quinoxalin-2(1H)-ones is achieved for the synthesis of (Z)-enaminones and furo[2,3-b]quinoxalines using the combination of a copper catalyst and an oxidant. This new protocol features mild reaction conditions, readily available materials, and a broad substrate scope. Gram-scale and mechanistic studies were also investigated. Furthermore, the desired products exhibited excellent antitumor activity against A549, HepG-2, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In the past decade, transition-metal-catalyzed inert C–H activations have been proven to be powerful strategies for many useful transformations and organic synthesis . Meanwhile, the directing-group-assisted C–H activation strategy has attracted significant attention .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, transition-metal-catalyzed inert C–H activations have been proven to be powerful strategies for many useful transformations and organic synthesis . Meanwhile, the directing-group-assisted C–H activation strategy has attracted significant attention .…”
Section: Introductionmentioning
confidence: 99%
“…The latest advances with the insertion of SO 2 concentrate on the radical process, and a series of radical precursors including phenylpropynoates, electron-deficient olefins, and indolyl-ynones were used for SO 2 insertion, inducing the formation of sulfonyl radical intermediates. Inspired by this outstanding work and as part of our ongoing interest in organic synthetic chemistry, herein, we reported a copper-catalyzed N–H sulfonylation reaction of sulfoximines, aryldiazonium tetrafluoroborates, and DABSO, providing the N -sulfonyl sulfoximines in high yields under mild conditions (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a genome-wide association study (GWAS) conducted using a panel of 529 rice accessions indicated that GHD7 and NAL were the major loci controlling the natural variation of chlorophyll content in rice leaves (Wang et al, 2015). Recently, GWAS was carried out for 29 rice leaf traits related to leaf size, shape, and color and unraveled several QTLs (Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%